2021
DOI: 10.1186/s12874-021-01357-z
|View full text |Cite
|
Sign up to set email alerts
|

The effect of home visits as an additional recruitment step on the composition of the final sample: a cross-sectional analysis in two study centers of the German National Cohort (NAKO)

Abstract: Background Participation in epidemiologic studies has been declining over the last decades. In addition to postal invitations and phone calls, home visits can be conducted to increase participation. The aim of this study was therefore to evaluate the effects of home visits in terms of response increase and composition of the additionally recruited and final sample. Methods In the framework of the German National Cohort (NAKO) recruitment process, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…In an additional effort, potential respondents were even visited at home. In a previous analysis, we demonstrated that those recruited with the extensive efforts of home visits did not differ from those recruited before ( 36 ). In the DigiHero study, only a single invitation was sent, accepting a lower response at higher efficiency.…”
Section: Discussionmentioning
confidence: 72%
“…In an additional effort, potential respondents were even visited at home. In a previous analysis, we demonstrated that those recruited with the extensive efforts of home visits did not differ from those recruited before ( 36 ). In the DigiHero study, only a single invitation was sent, accepting a lower response at higher efficiency.…”
Section: Discussionmentioning
confidence: 72%
“…In addition to considerations related to single assessments, there is also a longitudinal perspective. Although further efforts during recruitment (e.g., through reminder letters, phone calls, and home visits) result in an increase in response proportions [5,6,19,20], studies have indicated that participants recruited with more effort drop out earlier and are therefore of limited benefit for longitudinal studies [10,18]. These participants may be different from those who remain in the study, but if they are lost, there is not much that can be done to control for this selection.…”
Section: Introductionmentioning
confidence: 99%